Biopolitics in critical tourism theory: a radical critique of critique - Rodanthi Tzanelli (Via@)
The article reviews the uses of the concept of biopolitics in critical tourism studies. After a brief genealogical account of the concept in political philosophy, it follows its transposition and its thematic applications in tourism theory and practice. It is argued that biopolitics is only one of the three key domains of ‘human interests’, which must be subjected to a radical critique in tourism studies and practice. Such critique should be entwined with questions of (a) institutional and discursive power in the making of tourism worlds and destinations (‘worldmaking’ – Hollinshead, 2009a), but also, crucially (b) the analogous counter-discourses instituted by critical tourism studies scholars, who seek to legitimise their own epistemic community and thus produce a majoritarian voice endorsing an apparent (but not interest or motivation free) support of morally just causes for a better human and planetary futures.